Comprehensive profiling of extrachromosomal circular DNAs in colorectal cancer progression - Lu Lu; Mingjie Chen; Guicheng Zhang; Yujing Liu; Xiangyuan Xu; Zenghua Jiang; Yangxian Xu; Tao Liu; Fan Yang; Guang Ji; Hanchen Xu (Scientific Reports)
Abstract Colorectal cancer (CRC) development involves a series of molecular events that drive the progression from normal colorectal epithelium to adenoma and eventually to invasive carcinoma. While the involvement of extrachromosomal circular DNAs (ecDNAs) in cancer genome remodeling has been established, their specific roles in CRC formation remain unclear. Using Circle-Sequencing and whole transcriptomic sequencing, we comprehensively profile circular DNAs and transcriptomes in healthy individuals, colorectal adenoma, and CRC patients. Our delineate analyses characterize the key circular DNAs involved in oncogene expression through the normal-adenoma–carcinoma continuum and highlight that immune response-related pathways and cell cycle pathways, are the dominat events in CRC progression. Notably, chr8 ecDNA 64950741–114379093 exhibits robust up-regulation during CRC progression. Further validation in a new cohort of 50 CRC patients confirms the higher expression of chr8 ecDNA 64950741–114379093 and its strong correlation with poor prognosis. Thus, these findings provide unprecedented insights into the landscape of circular DNAs in CRC and highlights the potential of chr8 ecDNA 64950741–114379093 as a promising biomarker and therapeutic target for CRC management.